Formation of healthy lifestyle among schoolchildren with overweight and obesity - Palladina O.L (Kharkov National Pedagogical University, 2013)
The problem of overweight and obesity in school children is considered. It is shown that the problem of child obesity underlie the development of many serious medical illness. It is introduced the analysis of publications on the problem of overweight and obesity in schoolchildren. It is defined methods for detection and possible non-pharmacological correction of the condition. The necessity of creating and putting into practice of long-term training programs to promote healthy lifestyle among schoolchildren are overweight or obese, to prevent the development of cardiovascular disease and other metabolic complications. Conceptually, it is determined the main directions of teaching and physical education students who are overweight and obese. It is shown that it is advisable to inform children and parents about the need to combine a balanced diet with exercise stress.